Constructivism in Education with Teaching Logic in Universities of Viet Nam - Hieu, Tran Minh (RA Journal of Applied Research, 2021)
According to our survey, most students are not interested and afraid of Logic. Every year, over 700,000 university and college students have to study this subject out of nearly 2 million students of 521 universities and colleges (Ministry of Education and Training 2020). The logic course consists of about 2-4 credits, depending on the program structure of each university. Thus, the impact of the study of Logic on the general knowledge of students is not tiny. So how to improve the quality of teaching and learning this subject? In this paper, we will present some answers to this question, using Constructivism in teaching.